2008
DOI: 10.3113/fai.2008.1209
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Correction in Scarf and Chevron Osteotomy in Moderate and Severe Hallux Valgus: A Randomized Controlled Trial

Abstract: In patients with moderate and severe hallux valgus, the results of chevron osteotomy were at least as effective as a scarf osteotomy. Recurrent subluxation of the first metatatarsophalangeal joint was the main cause for insufficient correction. We favor the chevron osteotomy because it is less invasive, without sacrificing correction of HVA and IMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 16 publications
4
77
1
5
Order By: Relevance
“…In general, DMO is recommended for mild to moderate HV [4,29]. However, there are some studies recommended DMO in moderate to severe HV also [11,13]. Our study supports results of effective pain relief and increased functional ability in moderate to severe HV patients who underwent either PMO or DMO.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In general, DMO is recommended for mild to moderate HV [4,29]. However, there are some studies recommended DMO in moderate to severe HV also [11,13]. Our study supports results of effective pain relief and increased functional ability in moderate to severe HV patients who underwent either PMO or DMO.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, Saro et al [12] analyzed 100 patients with moderate to severe HV who underwent different techniques of distal metatarsal osteotomies and recommend the procedure only in patients with mild to moderate deformity. To our knowledge, the only investigation comparing distal and metatarsal osteotomy for moderate to severe HV is the Deenik et al article [13], which reported no different results in a randomised comparison between distal and proximal osteotomy in hallux patients; however, their conclusion was limited by sample size, which leads to a lower power, and clinical outcome comparison. Their conclusion as to whether or not to perform distal or proximal metatarsal osteotomy in moderate to severe HV remains controversial.…”
Section: Introductionmentioning
confidence: 96%
“…Hallux valgus surgery is a very common forefoot operation, and several techniques have been introduced to correct the deformity [1][2][3][4][5][6][7][8][9][10][11]. Hallux valgus often leads to pain, deformity of the big toe and secondary complications such as abnormal gait and ulcers on the foot.…”
Section: Introductionmentioning
confidence: 99%
“…Saro ve arkadaşları lindgren yöntemi ile chevronu karşılaştırmışlar herhangi bir fark görememişler, hafif vakalarda her iki yönteminde uygun olduğu sonucuna varmışlardır [73]. Deenik ve arkadaş-ları scarf osteotomi ile chevronu karşılaştırmışlar, her ikisin sonucunda anlamlı bir fark görememişler [74]. Pentikainen ve arkadaşları chevron osteotomisinde fiksasyon ile fiksasyon yapmadan elastik bandaj ile takip sonuçlarını değerlendirmişler ve 3.9 mm yer değiştirilip fiksasyon yapılan ve 3.1 mm yer değiştirilip fiksasyon yapıl-mayan grupta aynı klinik sonuca ulaşmışlardır [75].…”
Section: Chevron Prosedürüunclassified